2007 Proceedings 57th Electronic Components and Technology Conference 2007
DOI: 10.1109/ectc.2007.374039
|View full text |Cite
|
Sign up to set email alerts
|

Board Design Influence on BGA Mechanical Reliability

Abstract: With the technology trend moving towards faster, smaller, and cheaper products, the consumer electronics industry is using more and more high density fine pitch BGA components in a lead-free environment. This has created additional board-level solder joint mechanical reliability challenges. Current literature studies mostly focus on the impact of component design features on BGA solder joint reliability. Very little information is available on board design factor impact on BGA mechanical reliability. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The experimentally obtained PCB resonance frequency is validated by the FEM results. A similar technique is used in [27,28].…”
Section: Vibration Measurement Sensorsmentioning
confidence: 99%
“…The experimentally obtained PCB resonance frequency is validated by the FEM results. A similar technique is used in [27,28].…”
Section: Vibration Measurement Sensorsmentioning
confidence: 99%
“…Several previous studies have focused on securing the mechanical safety of a solder joint under vibration excitation by applying mitigation techniques to the package, such as applying an underfill or dummy solder balls [6][7][8]. Kim and Hwang [6] investigated the effect of underfill on the fatigue life of a plastic ball grid array (PBGA) package for space usage under random vibration excitation of the launch.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the fatigue test under harmonic vibration showed that applying dummy solder balls improved the fatigue life of the given SSD by 4.5 times by reducing the stresses on the functional solder balls. Uppalapati et al [8] investigated the sensitivity of three critical PCB design factors on the mechanical safety of the solder joint of a flip-chip ball grid array under vibration during shipping. The results showed high sensitivity with respect to the location of the package on the PCB, trace routing orientation of the PCB under the package, retention mechanism design, and mass of the heat sink.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the high-pin count package over 200 pins is desired more for high profit products, the ball-grid-array (BGA) package technology [1,2] is dramatically raised up in assembly industry. Because of the high power consumption in BGA type, some products requiring the high stability operation need a heat sink as an assistant to dissipate more Joule heat.…”
Section: Introductionmentioning
confidence: 99%